Recanalization After Radio-frequency Ablation (RFA) in Limb Varices at Dr. Cipto Mangunkusumo and Fatmawati General Hospitals from 2015- 2017 - Hermansyah, Rudi; Pratama, Dedy; Irfan, Witra (UI Scholars Hub, 2019)
Introduction. Ligation in upper location and stripping of the varicose veins, enfacing high incidence of failure, recanalization. Endovascular surgery is a modality used to treat limb varicose. However, the recanalization following the procedure was never evaluated. Method. We ran a cohort study on subjects with reflux of the great saphenous vein treated by RFA. Following the RFA procedure, the evaluation proceeded using ultrasound within the first three weeks. Results. A total of 77 subjects were analysed for recanalization post-RFA. Recanalization was found in one subject (1.3%), partial recanalization in 6 subjects (7.79%), and no recanalization in 70 subjects (90.9%). No significant difference between the diameter of the great saphenous vein with the procedure (p <0.001). Conclusion. We concluded that RFA is effective in treating limb varicose. In addition, we found there is no association between recanalization and age, sex, and body mass index statistically.